Guilt, reincarnation and the new paradigms of science - Bianeck, Desirée Varella (2012)
This article examines the question of guilt and its understanding in the field of religion regarding the design of reincarnation, considering relevant to objectify the division between the objectivity of positivist sciences and the object of study of so-called humanities. Addressing the theme of reincarnation, it intends to make way for an anti-hegemonic and emerging thinking about the separation between religion and science and the nature of the Eastern and Western science of psychology, Eastern. It starts with the assumption that the emergence of new paradigms for the sciences generally affect the psychology of expanding her existing views allowing their growth and enrichment through different parameters for the study of man/nature/society.